(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study aims to identify the experience of different types of risk,and techniques used to identify and reduce the risk in Saving and Credit Cooperative Societies (SAACOS) of the Kaski District of Nepal. Methods: The study employed a descriptive research design and along with a quantitative nature of data. Primary sources of data were collected through self-administered close-ended questions distributed to managers/managing/directors/accountants/BOD members of 190 sample cooperatives out of 370 saving and credit cooperatives of the Kaski district using a simple random sampling design. To conclude in line with the stated goals, percentages, mean, standard deviation, and frequencies were employed. Results: Most of the cooperatives concentrate loans to real estate businesses (38.9%), followed by business(34.7%), and household loans(19.5%). Similarly, the highest level of irregular loans in the real estate sector followed household loans (27%), business (23.8%) vehicles (19.4%), and agriculture and auto loans(5.9%).As the risk experience mean of credit risk (4.11)is higher than others, credit risk is the most prominent risk faced by these institutions. The cooperatives use internal audits, financial statement analysis,and external auditing to identify risk. The cooperatives heavily rely on well-trained board members, economic analysis, and trustworthiness in borrowers as risk mitigation tools. Conclusion: The study highlights the necessity for integrated risk management strategies that consider new risks and uncertainties, suggesting that cooperatives should adopt more comprehensive risk identification and mitigation approaches to enhance their resilience and sustain member value.